The influence of bed material grain size on scouring for labyrinth side weir flow - Tunc, Mustafa; Emiroglu, Muhammet Emin (TUBITAK, 2020)
In an alluvial stream bed, there is a continuous sediment movement depending on the flow. A new type of side weir built in a stream, the labyrinth side weir, can be discharged much more than the conventional weirs. This situation increases the importance of labyrinth weir for flood control. Although the effect of the weir type on the depth of equilibrium scour depth is large, the grain size of the bed material has a large influence on the scouring and the sediment bedform. In this study, it is aimed to investigate how the median grain size of the bed material affects the depth of equilibrium scour depth. For this purpose, the process of reaching equilibrium scour depth around the labyrinth side weir along with the discharge change using bed materials with different median grain sizes has been studied in detail. It has been concluded that the depth of the equilibrium scour depth decreases at different ratios as the median grain size increases with the effect of the flow intensity on the scouring being large. © 2020, TUBITAK. All rights reserved.
Labirent yan savak akımı için taban malzemesi boyutlarının oyulmaya etkisi
Keywords: Bed material; Equilibrium scour depth; Grain size; Hydraulic structure; Labyrinth side weir